Perancangan Aplikasi Pengelolaan Data Pinjaman Menggunakan Metode Terstruktur pada Koperasi Indosurya Simpan Pinjam Sukabumi - Wawang adi darma; Deny Ariestiandy (JURNAL BUANA INFORMATIKA CBI, 2020)
Abstract Indosurya Savings and Loans is a business entity located at Jl. A Yani No.29 Cikole Sukabumi City by moving in the field of savings and loans. In its development often encountered an error caused by lack of accuracy in the calculation of customer savings and loan data, and the possibility of fraud in work.The author wants to find out what affects the performance of the cooperative's activities, then the writer often encounters errors when making a final monthly report on customer deposits and loans. The author found errors in the data that is not synchronous savings and loans, and the authors also often encounter errors in the calculation of the sum of deposits and deposits because they are still recorded in the books. This is because all transactions carried out using methods that still rely on the performance of human resources. While sufficiently processed savings and loan data will affect time and energy efficiency.Knowing the importance of the above, the support of a fast and accurate information system is really needed by Indosurya Savings and Loans, therefore to overcome this problem the author makes or builds a system that will be able to collect savings and loan data appropriately, as well as managing bookkeeping data compulsory borrowing of members so that later they will produce quality reports. This system, will be made using Delphi XE2 and MY SQL Programming. Keywords: Application, Cooperative, Savings and Loans, Delphi XE2, MySql